Recovering Ponzi Scheme Losses and Integrating Victim Impact Statement in Indonesia’s Criminal Justice System - Anggriawan, Rizaldy (PRAWO i WIĘŹ, 2025)
The protection of victims’ rights within Indonesia’s criminal justice system remains inadequate, particularly in complex financial crimes such as Ponzi schemes. Despite the legal framework established by Law No. 31 of 2014 on Witness and Victim Protection (UU PSK), victims often struggle to recover their losses due to systemic weaknesses, limited enforcement, and regulatory inconsistencies. Cases like the Budi Hermanto gold investment fraud and the Binomo investment scam illustrate the failure of asset confiscation and restitution mechanisms, leaving victims without proper compensation. This study aims to analyze the role of the Public Prosecutor in victim loss recovery, evaluate restitution and compensation mechanisms, and identify key legal obstacles to effective victim protection. A significant recommendation is the implementation of the Victim Impact Statement (VIS), which would allow victims to convey the emotional and financial effects of crimes in court, potentially influencing judicial decisions and improving the fairness of rulings. A comparative analysis with legal frameworks in the United States and Hungary highlights Indonesia’s lagging victim compensation policies. The study concludes that strengthening prosecutorial involvement, refining restitution regulations, and integrating the VIS into judicial proceedings could significantly enhance victim rights and financial recovery. Such reforms are essential to ensure that justice is served to both perpetrators and victims, prioritising their restitution and protection.